A Fully Integrated Infectious Diseases and Antimicrobial Stewardship Telehealth Service Improves Staphylococcus aureus Bacteremia Bundle Adherence and Outcomes in 16 Small Community Hospitals. (14th October 2022) - Veillette, John J; May, Stephanie S; Gabrellas, Alithea D; Gelman, Stephanie S; Albritton, Jordan; Lyons, Michael D; Stenehjem, Edward A; Webb, Brandon J; Dalto, Joseph D; Throneberry, S Kyle; Stanfield, Valoree; Grisel, Nancy A; et al.
Abstract: Background: Infectious diseases (ID) and antimicrobial stewardship (AS) improve Staphylococcus aureus bacteremia (SAB) outcomes. However, many small community hospitals (SCHs) lack on-site access to these services, and it is not known if ID telehealth (IDt) offers the same benefit for SAB. We evaluated the impact of an integrated IDt service on SAB outcomes in 16 SCHs. Methods: An IDt service offering IDt physician consultation plus IDt pharmacist surveillance was implemented in October 2016. Patients treated for SAB in 16 SCHs between January 2009 and August 2019 were identified for review. We compared SAB bundle adherence and outcomes between patients with and without an IDt consult (IDt group and control group, respectively). Results: A total of 423 patients met inclusion criteria: 157 in the IDt group and 266 in the control group. Baseline characteristics were similar between groups. Among patients completing their admission at an SCH, IDt consultation increased SAB bundle adherence (79% vs 23%; odds ratio [OR], 16.9; 95% CI, 9.2–31.0). Thirty-day mortality and 90-day SAB recurrence favored the IDt group, but the differences were not statistically significant (5% vs 9%; P = .2; and 2% vs 6%; P = .09; respectively). IDt consultation significantly decreased 30-day SAB-related readmissions (9% vs 17%; P = .045) and increased length of stay (median [IQR], 5 [5–8] days vs 5 [3–7] days; P = .04). In a subgroup of SAB patients with a controllable source, IDt appeared to have a mortality benefit (2% vs 9%; OR, 0.12; 95% CI, 0.01–0.98). Conclusions: An integrated ID/AS telehealth service improved SAB management and outcomes at 16 SCHs. These findings provide important insights for other IDt programs. Abstract : An integrated infectious disease and antimicrobial stewardship telehealth service improved Staphylococcus aureus bacteremia management and outcomes at 16 small community hospitals. These findings provide important insight for other IDt programs.